EFFECT OF MICROSURGICAL VARICOCELECTOMY ON SEXUAL FUNCTIONS OF INFERTILE MALES. - S. I. Gamidov; R. I. Ovchinnikov; A. Yu. Popova; D. V. Scherbakov; S. Kh. Izhbaev (Вестник урологии, 2015)
Varicosity of testicular veins is a widespread urological disease and one of the most common reasons of male infertility. In 40-80% changes in sperm parameters may be the only clinical sign of varicocele. Some literature data report on the fact that varicocele leads to the decrease of testosterone level and worsening of erectile function, and varicocelectomy contributes to testosterone levels elevation and improvement of erection. We compared the effect of microsurgical varicocelectomy and stimulation of spermatogenesis on the sperm parameters, sexual function and hormonal levels in males with varicocele suffering from sexual disorders and infertility.Microsurgical varicocelectomy leads to testosterone elevation by 47.2%, decrease of estradiol by -3.1%, of progesterone by -2.3% by the end of the 12th month after operation, and stimulation of spermatogenesis increases testosterone levels by 10.8%, decreases estradiol by -8%, progesterone by -2.8% during the same period. In the group of surgical treatment concentration of spermatozoa increased 2.5 –fold as much, and in the group of stimulation 1.5-fold only. Questionnaire data demonstrated that the mean index “erectile function” in operated patients increased by 46.2%, “orgasm” increased by 21.5%, index “general satisfaction” by 39.3%, index “satisfaction with sexual act” by 35%, index “libido” improved by 26.6%. In the group of stimulation of spermatogenesis similar indexes were as follows: erectile function improved by 20.6%, orgasm by 7.4%, general satisfaction by 8%, satisfaction with sexual act by 13.6%, libido by 8.9%. According to AMS questionnaire in the group of varicocelectomy summarized scores decreased by 8%, in stimulation group only by 2%. Moreover a summarized enlargement of testicular volume was by 41.1% better in the group of operative interventions and by 5.2% in the group of spermatogenesis stimulation.